Analisis Model UTAUT Terhadap Penggunaan Digital Payment Pada Wisatawan Pariwisata Unggulan Di Sumatera Barat - Alif Revan Dynel Aurallie; Heru Aulia Azman (CV. ITTC INDONESIA, 2026)
This study aims to analyze the factors influencing domestic tourists’ intention and actual behavior in using digital payment systems at leading tourism destinations in West Sumatra Province by employing the Unified Theory of Acceptance and Use of Technology (UTAUT) model, extended with the habit variable. A quantitative research approach with a survey method was adopted in this study. Data were collected through the distribution of questionnaires to 390 domestic tourists who had visited leading tourism destinations in West Sumatra. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The findings of this study are expected to provide both theoretical and practical contributions to the development of the digital payment ecosystem in the regional tourism sector.